Lifelong Wellbeing in the World (WELLSO-2014) International Scientific Symposium Proceedings, Tomsk, 28-30 April 2014 - Barysheva Economist Professor of Tomsk Polytechnic University, Doctor of economic sciences (DSc); Borisova (TPU Publishing House, 2014)
The publication presents the results of current scientific research of Russian and foreign scientists, teachers, post-graduates and students. All studies are united by the one goal - to create conditions for the human welfare. The consideration of the problem of assessment and management of welfare is based on the multi disciplinary approach of Economics and Sociology, Medicine and Psychology, Physical culture and sports, IT technology. Special attention is paid to the welfare of the elderly, social media, ageing of the population. Also consider the financial, social and environmental aspects of wellbeing.